2017
DOI: 10.3389/fcimb.2016.00204
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Genomics of the Zoonotic Pathogen Ehrlichia chaffeensis Reveals Candidate Type IV Effectors and Putative Host Cell Targets

Abstract: During infection, some intracellular pathogenic bacteria use a dedicated multiprotein complex known as the type IV secretion system to deliver type IV effector (T4E) proteins inside the host cell. These T4Es allow the bacteria to evade host defenses and to subvert host cell processes to their own advantage. Ehrlichia chaffeensis is a tick-transmitted obligate intracellular pathogenic bacterium, which causes human monocytic ehrlichiosis. Using comparative whole genome analysis, we identified the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These integrated approaches led to the effective identification of several bacterial virulence determinants (e.g. effectors and regulators) and their diverse mechanisms of action (Cheng et al, 2008;Rikihisa, 2017;Marcelino et al, 2015b ;Moumene et al, 2017;Noroy and Meyer, 2017;Noroy and Meyer, 2021). Notably, Rikihisa et al identified that the EtpE protein governs the binding and entry of E. chaffeensis into its host cells (Mohan Kumar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These integrated approaches led to the effective identification of several bacterial virulence determinants (e.g. effectors and regulators) and their diverse mechanisms of action (Cheng et al, 2008;Rikihisa, 2017;Marcelino et al, 2015b ;Moumene et al, 2017;Noroy and Meyer, 2017;Noroy and Meyer, 2021). Notably, Rikihisa et al identified that the EtpE protein governs the binding and entry of E. chaffeensis into its host cells (Mohan Kumar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid increase in high-quality genomes, the application of comparative genomics is more and more extensive and in-depth (Setubal et al, 2018). So far, comparative genomics has been used in various species such as the Zoonotic pathogen Ehrlichia chaffeensis, revealing candidate effectors and putative host cell targets (Noroy and Meyer, 2017). The complete genome of seven highly virulent Xanthomonas.…”
Section: Introductionmentioning
confidence: 99%
“…Liberty. This effector appears to be involved in the differential inter-strain virulence observed between Arkansas and Liberty strains in SCID mice (Noroy and Meyer, 2016). Moreover, some intense recombination events between E. ruminantium strains have been discovered, which may facilitate bacterial adaptation for survival and adaptation under various environmental conditions in both vector and host species (Cangi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%